Project-based learning using a laboratory approach on learning outcomes and critical thinking in marine biology - Hasan Tuaputty; Saiful Alimudi; Anthony Kudjo Donkor; Ine Arini; Louvenska Nona Latupeirissa (University of Muhammadiyah Malang, 2023)
The learning process must actively involve students and provide opportunities for them to study and prove the theories they learn. This study determined the influence of the application of Project-Besad Learning (PjBL) using a laboratory approach on learning outcomes and critical thinking in marine biology. This study used a descriptive quantitative method, with the independent variable being the implementation of PjBL with a laboratory approach and involved 32 students in the sixth semester of Biology Education at Pattimura University Indonesia enrolled in marine biology courses. The dependent variables were students' learning outcomes and critical thinking, and the data were collected by tests (knowledge and critical thinking) and observations (attitude and skill). The analysis revealed that the integration of the PjBL with a laboratory approach had a weak effect on knowledge (0.003 <p 0.005), a moderate effect on attitude and skill (0.000 <p 0.005), and a strong effect on critical thinking. The regression analysis showed that there was a correlation between the independent variable and student knowledge (R2 = 0.257 or 25%), attitude (R2 = 0.471 or 47.1%), psychomotor/skill (R2 = 0.470 or 47%), and critical thinking (R2 = 0.934 or 93.4%). In conclusion, the implementation of PjBL using a laboratory approach can improve student learning outcomes and critical thinking in marine biology.